Evaluation of emotional expression, psychiatric symptoms, burnout, hopelessness and depression in relatives of substance dependent patients - Guliz Senormanci; Cetin Turan; Omer Senormanci; Rustem Askin (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The aim of the study was to compare psychiatric symptoms, burnout, hopelessness and depression between first-degree caregivers of dependent patients and control groups and to investigate the relation between emotional expression, psychiatric symptoms, burnout, hopelessness, depression and clinical features in relatives of the dependent group. The sample consisted of 40 participants who were primary caregiving relatives of dependent patients with history of at least one year dependence and being treated for dependence in in-patient or out-patient clinics and 40 participants with similar age, education year, gender, and marital status with relative group and with no history of psychiatric admission. Written informed consent was provided and demographic data form, Symptom Checklist-90-Revised (SCL-90-R), Beck Depression Scale (BDS), Beck Hopelessness Scale (BHS), Maslach Burnout Inventory (MBI) were administered. Expressed Emotion Scale (EES) was only administered in relatives of the dependent group. In the present study, negative expectation score and total score of BHS were significantly higher than the control group in relatives of dependent patients. SCL-90-R somatization, interpersonal sensitivity, depression, anxiety and additional scales scores of the relatives of dependent patients were significantly higher than the control group. There was a positive correlation between the education year and the EES subscales and total scores. There was a positive correlation between the EES overprotective attitudes and total score of BHS. There was a negative correlation between BHS total score and the EES judgmental/hostile attitudes and additional scales.As a result, being relatives of patients with dependence was found to be associated with burnout, depression, hopelessness, and the risk of developing mental illness. [JCBPR 2019; 8(1.000): 33-42]